Ibiza (Balearen), Spanien: Der römische Schiffsfund von Grum de Sal - Hermanns, Marcus H. (e-Forschungsberichte des DAI, 2023)
The Roman shipwreck of Grum de Sal was monitored several times during the work of the inventory of underwater archaeological sites and finds around the Pithyusic Islands (Ibiza and Formentera) which were mainly conducted from 2006 to 2012. The site showed to be highly exposed to both anthropogenic and marine influences. The focus of the two-week preliminary campaign in october of 2013 was therefore the status analysis of this archaeological context with a view to a future final examination. At the same time, a pneumatic drilling system for sampling wood cores for dendrochronological analysis was tested under water.